Implementation Of Financial Accounting Standards For Entities Without Public Accountability: A Comparative Literature Review - Nika Selvia; Cakti Indra Gunawan; Budi Hariono (International Journal of Management and Business, 2026)
This study investigates the progression of scholarly literature concerning the implementation of Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) over the period 2015 to 2025. Employing a descriptive analytical approach, the research incorporates literature comparison and triangulation methods to synthesize findings. The results indicate that approximately 80% of theoretical and empirical developments related to the application of SAK ETAP—particularly within Small and Medium Enterprises (SMEs) and cooperatives—remain concentrated on several key areas: the analysis and enhancement of implementation practices, training initiatives, governmental support mechanisms (such as public dissemination), and the educational backgrounds of stakeholders involved in preparing financial statements in accordance with SAK ETAP. This is substantiated by a review of literature on SAK ETAP from 2015 to 2025, which continues to reflect a gap in theoretical advancement. Notably, the research has yet to explore the development of SAK ETAP theory influenced by the online software system introduced by the central government through the Directorate General of Taxes. Furthermore, a newly emerging framework known as the Private Entity SAK has been introduced as of early 2025, signaling a potential shift in the regulatory landscape.